The Relationship Between Marriage Age, Parity, and Hormonal Contraceptive Use With Cervical Cancer Incidence at NTB Provincial Hospital - Ni Luh Made Candra Wati; Hilda Santosa; I Gede Angga Adnyana; Adib Ahmad Shammakh (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background: Cervical cancer is the most common health problem affecting the female reproductive system. It is caused by infection with the Human Papillomavirus (HPV). The most common risk factors for cervical cancer are age at marriage, parity, and use of hormonal contraceptives. Objective: To analyze the relationship between age at marriage, parity, and hormonal contraceptive use with cervical cancer incidence at the NTB Provincial General Hospital. Methods: This quantitative study used a case-control design. The sampling technique used purposive sampling with a sample size of 110 samples. Data were taken from medical records at the NTB Provincial Hospital. Data were analyzed using the Chi-square test with a significance limit of p-value <0.05.Results: It was found that most of the respondents married at the age of ≥20 years, as many as 69 (62.7%), had parity ≤3 times as many as 80 (72.7%), and used hormonal contraception as many as 58 (52.7%). The Chi-square test showed a significant relationship between age at marriage (p-value = 0.002; OR = 3,997; 95% CI = 1.742-9.170), parity (p-value = 0.005; OR = 3,917; 95% CI = 1.555-9.863), and use of hormonal contraception (p-value <0.001; OR = 4.618; 95% CI = 2.066-10.327) with the incidence of cervical cancer. Conclusion: Age at marriage, parity, and use of hormonal contraception were significantly associated with the incidence of cervical cancer at the NTB Provincial Hospital.